Organometallic photoresist developer compositions and processing methods

By using improved chemical development compositions and specific solvent mixtures, the problem of microbridges and other defects in semiconductor device preparation in prior art is solved, achieving higher pattern defect density and high resolution.

JP2025072424APending Publication Date: 2025-05-09INPRIA CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025012863
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-04-12
Filing Date
2025-01-29
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce microbridges and other defects when preparing semiconductor devices and other complex structures, affecting the high-density integration and functionality of the device.

Method used

Microbridges and other defects are reduced by using an improved chemical development composition by using a solvent mixture consisting of at least two solvents as the developer. The solvent mixture contains more than 55% of the base solvent and 0.25% to 45% of the polar solvent, such as water, alcohol, glycerol ether, pyrrolone, lactic acid or carboxylic acid.

Benefits of technology

The density of microbridges and other defects in high-density integrated circuits is significantly reduced, the density of pattern defects is improved, and the high resolution and high accuracy of pattern are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025072424000004
    Figure 2025072424000004
  • Figure 2025072424000005
    Figure 2025072424000005
  • Figure 2025072424000006
    Figure 2025072424000006
Patent Text Reader

Abstract

SOLUTION: Developer compositions are described based on blends of solvents, where the developers are particularly effective for EUV patterning using organometallic based patterning compositions. Methods for use of these developing compositions are described. The blends of solvents can be selected based on Hansen solubility parameters. Generally, one solvent has low polarity as expressed by the sum of δP+δH, and a second solvent component of the developer has a higher value of δP+δH. Corresponding solvent compositions are described.EFFECT: The compositions and materials disclosed herein enable the formation of high-fidelity patterns and structures with improved, i.e., reduced, pattern defect density, such as microbridging, in lithographic processing of organometallic photoresists.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to pending U.S. Provisional Patent Application No. 62 / 833,343, entitled “Organometallic Photoresist Developer Compositions,” filed April 12, 2019 by Jiang et al., the contents of which are incorporated herein by reference.

[0002] Technical Field The present invention relates to improved processing of organometallic radiation patterning compositions to reduce defects. In particular, improved chemical developing compositions are described to reduce microbridging and similar defects. Post-development washes to reduce defects are also described. [Background technology]

[0003] For the formation of semiconductor-based devices, as well as other electronic devices or other complex precision structures, materials are typically patterned and integrated into structures. Thus, the structures are typically formed through a process that repeats a series of deposition and etching steps, through which patterns are formed from various materials. In this manner, multiple devices can be formed in a small area. Technological advances in the art can also reduce the footprint of devices, which may be desirable for improving performance.

[0004] Organic compositions can be used as radiation-patterned resists, whereby a radiation pattern is used to change the chemical structure of the organic composition corresponding to the pattern. For example, the process of patterning a semiconductor wafer can involve lithographically transferring a desired image from a thin film of an organic radiation-sensitive material. Patterning a resist typically involves several steps, such as exposing the resist to a selected energy source, such as through a mask, to record a latent image, followed by developing and removing selected areas of the resist. In the case of a positive resist, the exposed areas are transformed to make them selectively removable, whereas in the case of a negative resist, the unexposed areas can be more easily removed.

[0005] Typically, the pattern is developed using radiation, reactive gases, or liquid solutions to selectively remove sensitive portions of the resist while other portions of the resist act as an etch-resistant protective layer. Liquid developers can be particularly effective at developing the latent image. The substrate can be selectively etched through windows or gaps in the remaining areas of the protective resist layer. Alternatively, material can be deposited through the developed windows or gaps in the remaining areas of the protective resist layer onto the exposed areas of the underlying substrate. Finally, the protective resist layer is removed. Additional layers of patterned material can be formed by repeating the process. Materials can be deposited using chemical vapor deposition, physical vapor deposition, spin coating, or other desired approaches. Additional processing steps such as deposition of conductive materials or implantation of dopants can be used. In the field of micro- and nano-fabrication, the size of features in integrated circuits is becoming increasingly smaller to achieve higher integration densities and improved circuit functionality. Summary of the Invention [Means for solving the problem]

[0006] The compositions and materials disclosed herein enable the formation of high fidelity patterns and structures with improved, i.e., reduced, density of pattern defects, such as microbridging, in the lithographic processing of organometallic photoresists.

[0007] In a first aspect, a method for developing a radiation-exposed organometallic patterning layer to form a developed patterned layer comprising an organometallic oxide / hydroxide network is provided, the method comprising contacting the radiation-exposed organometallic patterning layer with a developer composition comprising a solvent blend. The solvent blend comprises at least two solvents, each independently having a sum of Hansen Solubility Parameters, δH+δP, of about 16 (J / cm 3 ) 1 / 2 At least 55% by volume of one or more solvents having a Hansen solubility parameter δH+δP of at least about 16 (J / cm 3 ) 1 / 2 The solvent is about 0.25% by volume to about 45% by volume of one or more of the solvents.

[0008] In yet another aspect, the invention relates to a method of developing a radiation-exposed organometallic patterning layer comprising an organometallic oxide / hydroxide network, the method comprising contacting the radiation-exposed organometallic patterning layer with a developer composition comprising from about 0.25% to about 45% by volume of a solvent blend of water, alcohol, glycol ether, pyrrolidone, lactone, carboxylic acid, or combinations thereof, and at least 55% by volume of a ketone, ether, ester, or combinations thereof.

[0009] The drawings contained in this application are incorporated in and constitute a part of the specification. The drawings illustrate embodiments of the present disclosure and, together with the description of the detailed description of the invention, serve to explain the principles of the present disclosure. The drawings are merely illustrative of certain embodiments and are not intended to limit the present disclosure. [Brief description of the drawings]

[0010] [Figure 1] A set of six scanning electron microscope (SEM) images of 32 nm pitch lines with 16 nm spacing patterned via EUV lithography. The bottom left, bottom center, and bottom right images show microbridging defects, while the top left, top center, and top right images are close-ups of the microbridging defects in the corresponding lower images. [Diagram 2] FIG. 1 is a plot of dose vs. gel value (Dg) vs. Hansen solubility parameters δH and δP for the solvents in Table 1, where Dg represents the measured EUV dose to the gel when each solvent was used as a developer for an organotin oxide hydroxide photoresist processed at a post-exposure bake (PEB) temperature of 160° C. [Diagram 3] 1 is a flow chart for a photolithography process according to an embodiment of the present disclosure. [Figure 4] A set of three H NMR spectra is shown: 2-heptanone (top), 10% by volume formic acid in 2-heptanone (middle), and 10% by volume formic acid in 2-heptanone (bottom) at time t=0, and t=1 week, respectively. The results show the stability of the formic acid solution over a one week time frame. [Diagram 5] Microbridge density (Def / Die 16p32) as a function of post-exposure bake temperature for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines is plotted for three developer compositions (2 vol. % formic acid in 2-heptanone, 10 vol. % formic acid in 2-heptanone, or 2-heptanone). [Figure 6] Microbridge density (Def / Die 16p32) as a function of equivalent dose density (16p32 Esize) for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines is plotted for three developer compositions: 2 vol. % formic acid in 2-heptanone, 10 vol. % formic acid in 2-heptanone, and 2-heptanone. [Figure 7]FIG. 1 shows a plot of line width roughness (LWR) as a function of equivalent dose density (16p32 Esize) for three developer compositions (2 vol.% formic acid in 2-heptanone, 10 vol.% formic acid in 2-heptanone, and 2-heptanone) for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines. [Figure 8] Microbridge density (Def / Die 16p32) at a target CD of 16 nm as a function of post-exposure bake temperature for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines is plotted for three developer compositions: 2 vol. % ethylhexanoic acid (EHA) in 2-heptanone, 10 vol. % EHA in 2-heptanone, and 2-heptanone. [Figure 9] Microbridge density (Def / Die 16p32) as a function of equivalent dose density (16p32 Esize) for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines is plotted for three developer compositions: 2 vol. % ethylhexanoic acid (EHA) in 2-heptanone, 10 vol. % EHA in 2-heptanone, and 2-heptanone. [Figure 10] Array of 12 scanning electron microscope (SEM) photographs of a silicon substrate with metalorganic resist patterned by EUV lithography to form 32 nm pitch lines, each photograph taken from a field with an average line CD closest to 16 nm, with the top row of four SEM photographs corresponding to a post-exposure bake (PEB) temperature of 140° C., the second row of four SEM photographs corresponding to treatment at a PEB temperature of 160° C., and the bottom row of four SEM photographs corresponding to treatment at a PEB temperature of 180° C., with the four images in each row corresponding, from left to right, to 2-heptanone (HF0), PGMEA (PF0), 10 vol. % formic acid in 2-heptanone (HF2), and 10 vol. % formic acid in PGMEA (PF2), respectively. [Figure 11]Array of 10 scanning electron microscope (SEM) photographs of a silicon substrate with metalorganic resist patterned by EUV lithography to form 32 nm pitch lines, each photograph taken from a field with an average line CD closest to 16 nm; the top row of five SEM photographs correspond, from left to right, to development with 2-heptanone (HF0), 5 vol. % formic acid in 2-heptanone (HF1), 10 vol. % formic acid in 2-heptanone (HF2), 15 vol. % formic acid in 2-heptanone (HF3), and 20 vol. % formic acid in 2-heptanone (HF4); and the bottom row of five images correspond, from left to right, to development with PGMEA (PF0), 5 vol. % formic acid in PGMEA (PF1), 10 vol. % formic acid in PGMEA (PF2), 15 vol. % formic acid in PGMEA (PF3), and 20 vol. % formic acid in PGMEA (PF4). [Figure 12A] Line width roughness (LWR) in nanometers as a function of line CD in nanometers at a post-exposure bake of 140° C. is plotted for four developer compositions (PGMEA, 2-heptanone, 10 vol. % formic acid in PGMEA, and 10 vol. % formic acid in 2-heptanone). [Figure 12B] Line width roughness (LWR) in nanometers as a function of line CD in nanometers at 160° C. post-exposure bake (temperature) is plotted for four developer compositions (PGMEA, 2-heptanone, 10 vol. % formic acid in PGMEA, and 10 vol. % formic acid in 2-heptanone). [Figure 12C] Line width roughness (LWR) in nanometers as a function of line CD in nanometers at 180° C. post-exposure bake (temperature) is plotted for four developer compositions (PGMEA, 2-heptanone, 10 vol. % formic acid in PGMEA, and 10 vol. % formic acid in 2-heptanone). [Figure 13]FIG. 11 is a log-linear plot of the estimated number of defects per 150 images (number of defects (18p32) / 150 images) as a function of equivalent dose vs. size value (16p32 Esize) for organometallic resists patterned with EUV lithography using developer compositions HF0-HF4 and PF0-PF4 at three post-exposure bake (PEB) temperatures. [Figure 14] Array of 18 scanning electron microscope (SEM) photographs of silicon substrates with metalorganic resist patterned by EUV lithography to form 32 nm pitch lines, each photograph taken from a field with an average line CD closest to 16 nm; the top row of four SEM photographs correspond to a post-exposure bake (PEB) temperature of 170° C., the second row of four SEM photographs correspond to processing at a PEB temperature of 180° C., and the bottom row of four SEM photographs correspond to processing at a PEB temperature of 190° C.; the four images in each row correspond, from left to right, to PGMEA (PF0), 1 vol. % acetic acid in PGMEA (PA1), 2 vol. % acetic acid in PGMEA (PA2), 5 vol. % acetic acid in PGMEA (PA3), 7.5 vol. % acetic acid in PGMEA (PA4), and 10 vol. % acetic acid in PGMEA (PA5), respectively. [Figure 15] FIG. 13 is a log-linear plot of the estimated number of defects per 150 images (Number of Defects (18p32) / 150 Images) for 18p32 patterns as a function of equivalent dose vs. size value (16p32 Esize) for an organometallic resist patterned with 32 nm pitch lines by EUV lithography for developer compositions PF0 and PF1-PF5 at three post-exposure bake (PEB) temperatures. [Figure 16] FIG. 1 is a plot of the estimated number of defects per 150 images (Defects(16p32) / 150 images) of 16p32 patterns as a function of equivalent dose vs. size value (16p32 Esize) for organometallic resists patterned by EUV lithography with developer compositions PF0 and PA1-PA5 at three post-exposure bake (PEB) temperatures. [Figure 17]FIG. 13 is a plot of the estimated number of defects per 150 images (Number of Defects (16p32) / 150 Images) of 16p32 patterns as a function of equivalent dose vs. size value (16p32 Esize) for organometallic resists patterned by EUV lithography with developer compositions HW1-HW4 at three post-exposure bake (PEB) temperatures. [Figure 18] 1 is a plot of the estimated number of defects per 150 images (number of defects (16p32) / 150 images) of a 16p32 pattern as a function of cleaning conditions for an organometallic resist patterned by EUV lithography, developed with 2 vol.% 1,2-hexanediol in 2-heptanone, and cleaned with various cleaning conditions: (A) no cleaning, (B) 15 s cleaning with 2-heptanone, (C) 15 s cleaning with 2 vol.% 1,2-hexanediol in 2-heptanone, or (D) 15 s cleaning with 2-heptanone followed by 15 s cleaning with 2 vol.% 1,2-hexanediol in 2-heptanone. [Figure 19] Representative SEM images and performance data for an organometallic resist patterned by EUV lithography to form hexagonal pillar patterns with pillar diameters of 23 nm, processed with a post-exposure bake temperature of 170 °C and 2-heptanone developer (left), a post-exposure bake temperature of 190 °C and 2 vol% acetic acid in PGMEA developer (center), and a post-exposure bake temperature of 190 °C and 5 vol% acetic acid in PGMEA developer (right). [Figure 20] Array of six scanning electron microscope (SEM) photographs of silicon substrates with metalorganic resist patterned by EUV lithography to form 32 nm pitch lines, each photograph taken from a field with an average line CD closest to 16 nm, the top row of three SEM photographs corresponding to a post-exposure bake (PEB) temperature of 160° C. and the bottom row of three SEM photographs corresponding to treatment at a PEB temperature of 180° C., with the three images in each row corresponding, from left to right, to 2-heptanone (HF0), PGMEA (PF0), PGME (PG0), and n-propanol (NP0), respectively. [Figure 21]FIG. 13 is a log-linear plot of the estimated number of defects per 150 images of an 18p32 pattern (Defects(18p32) / 150 images) as a function of equivalent dose versus size value (16p32 Esize) for an organometallic resist patterned by EUV lithography to form 32 nm pitch lines, with developer compositions of 2-heptanone (HF0), PGME (PG0), and n-propanol (NP0), and post-exposure bake (PEB) temperatures of 160° C. and 180° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Improved solutions as developers for organometallic photoresists have been found to reduce patterned defect density. Developer compositions are generally selected for their ability to enable high solubility contrast between exposed and unexposed areas of the photoresist. In other words, the developer can effectively translate the exposure-induced latent image in the photoresist coating into a physical pattern. The developer compositions disclosed herein contain a primary organic solvent that provides baseline negative tone development of exposed organometallic resists, and selected additives that have been found to improve pattern defectivity. In some embodiments, an amount of water, generally less than 1% by volume, may be optionally added to further aid in reducing defects. Desirable organic additives for the developer can generally be identified through their Hansen Solubility Parameters and / or their functional groups.

[0012] To obtain commercially desirable patterning results, it is generally desirable for the patterned material to have well-defined and high fidelity to achieve a particular functionality of the integrated device, such as electrical conductivity or capacitance. Defects such as holes or breaks in the pattern can be detrimental to the functionality of the device and can reduce the overall device yield. It is therefore desirable for the developed photoresist pattern to have high fidelity and sufficiently low defects such as undesirable bridging between adjacent features so that the patterned structures can be successfully integrated into a device or circuit. Thus, there is a demand for development methods and compositions that ultimately result in high fidelity patterns, i.e., patterns with low defect rates. It has been found that the presence of certain additive compositions can improve patterning properties, particularly in terms of reducing patterned defects such as micro-bridging and scum between features. Line width roughness (LWR) can also be improved, as shown in the examples below.

[0013] A new class of radiation-based resists may be based on metal oxide chemistries (metal oxo / hydroxo compositions) using radiation-sensitive ligands to control the stability and processability of the resist. Generally, these resist compositions function as negative photoresists when developed with organic solvents. In general, patterning of these metal-based compositions may benefit from the developers described herein. Related resist compounds are discussed in U.S. Pat. No. 8,703,386 B2 to Bass et al., entitled "Metal Peroxo Compounds With Organic Co-ligands for Electron Beam, Deep UV and Extreme UV Photoresist Applications," which is incorporated herein by reference. Although tin compositions are exemplified herein and the data presented herein focuses on tin-based resists, the developer compositions described herein are expected to be effective for other metal-based resists, as described below.

[0014] Organometallic photoresists, such as organotin oxide hydroxides, have been shown to have excellent properties as photoresists for use in lithographic photopatterning. Suitable organometallic photoresists include those described in U.S. Pat. No. 9,310,684 B2 to Meyers et al., entitled "Organometallic Solution Based High Resolution Patterning Compositions," U.S. Patent Application Publication No. 2016 / 0116839 A1 to Meyers et al., entitled "Organometallic Solution Based High Resolution Patterning Compositions and Corresponding Methods," and U.S. Pat. No. 10,228,618 B2, entitled "Organotin Oxide Hydroxide Patterning Compositions, Precursors, and Patterning," all of which are incorporated herein by reference. Other organometallic patterning compositions based on various metals are described in U.S. Patent Application Publication No. 2002 / 0076495 to Maloney et al., entitled "Method of Making Electronic Material," and U.S. Patent No. 9,372,402 B2 to Freedman et al., entitled "Molecular Organometallic Resists for EUV," both of which are incorporated herein by reference. Resists comprising metal oxide particles with an organic coating are described in U.S. Patent Application Publication No. 2015 / 0234272 A1 to Sarma et al., entitled "Metal Oxide Nanoparticles and Photoresist Compositions," which is incorporated herein by reference. Applicants have developed highly advanced developed organotin patterning materials, some of which are exemplified compositions.

[0015] Suitable organotin materials generally have the formula R z SnO (2-(z / 2)-(x / 2)) (OH) x (where 0 < z ≦ 2 and 0 < (z + x) ≦ 4, and R is a hydrocarbyl group having 1 to 31 carbon atoms or a blend with another R group, and for N separate compositions, R N and can be described as). It is based on the chemistry of radiation-sensitive patterning compositions. In the coating layer, the composition can be integrated into a common oxo / hydroxone network. In particular, branched alkyl ligands are desirable for some patterning compositions that can be represented by R 1 R 2 R 3 CSn(NR’)3 (where R 1 and R 2 are independently alkyl groups having 1 to 10 carbon atoms, and R 3 is hydrogen or an alkyl group having 1 to 10 carbon atoms). As shown below, this representation of the alkyl ligand R is generally R 1 R 2 R 3 CSn(X)3 (X corresponds to a trialkoxide or triamide moiety) and is similarly applicable to other embodiments. In some embodiments, R 1 and R 2 can form a cyclic alkyl moiety, and R 3 may be bonded to other groups in the cyclic moiety. Suitable branched alkyl ligands include, for example, isopropyl (R 1 and R 2 are methyl, and R 3 is hydrogen), tert-butyl (R 1 , R 2 , and R 3 are methyl), tert-amyl (R 1 and R 2 are methyl, and R 3 is -CH2CH3), sec-butyl (R 1 is methyl, R 2 is -CH2CH3, and R 3 is hydrogen), neopentyl (R 1 and R2 is hydrogen, and R 3 is -C(CH3)3), cyclohexyl, cyclopentyl, cyclobutyl, and cyclopropyl. Examples of suitable cyclic groups include, for example, 1-adamantyl (-C(CH2)3(CH)3(CH2)3 or tricyclo(3.3.1.13,7)decane bonded to the metal at a tertiary carbon) and 2-adamantyl (-CH(CH)2(CH2)4(CH)2(CH2) or tricyclo(3.3.1.13,7)decane bonded to the metal at a secondary carbon). In other embodiments, the hydrocarbyl group may comprise an aryl or alkenyl group, such as a benzyl or allyl group, or an alkynyl group. In other embodiments, the hydrocarbyl ligand R may comprise any group consisting of only C and H and containing 1 to 31 carbon atoms. In summary, some examples of suitable alkyl groups attached to tin include, for example, linear or branched alkyl groups (i-Pr((CH3)2CH-), t-Bu((CH3)3C-), Me(CH3-), n-Bu(CH3CH2CH2CH2-)), cycloalkyl groups (cyclopropyl, cyclobutyl, cyclopentyl), olefinic groups (alkenyl, aryl, allylic), or alkynyl groups, or combinations thereof. In yet another embodiment, suitable R groups may include hydrocarbyl groups substituted with heteroatom functional groups including cyano groups, thio groups, silyl groups, ether groups, keto groups, ester groups, or halogen-containing groups, or combinations thereof.

[0016] A precursor composition for forming an organotin oxo / hydroxyl coating composition that is integrated into a common oxo / hydroxo network may comprise one or more organotin oxo / hydroxo compounds or corresponding compounds having hydrolyzable ligands that form oxo and / or hydroxo ligands upon hydrolysis. In the case of a precursor composition having multiple compounds, the compounds may have distinct organic ligands with metal-carbon bonds and the same or distinct hydrolyzable ligands. Thus, a precursor composition for forming a radiation sensitive coating may comprise R n SnX 4-n(wherein n=1 or 2, R is a hydrocarbyl group having 1 to 31 carbon atoms, such as those described above, and X is a ligand having a hydrolyzable MX bond), and mixtures thereof. Suitable hydrolyzable ligands include, for example, alkynides RC≡C, alkoxides RO - , carboxylate RCOO - In particular, the organotin trialkoxide composition may include a compound represented by the formula RSn(OR 0 )3(wherein, R 0 The group may be one of the same moieties as described above for R. In some embodiments, the organotin precursor composition described above may be represented by MX4 and / or MO ((m / 2)-l / 2) (OH) l (In the formula, 0 <z≦2、0<(z+w)≦4であり、mはM m+The photoresists may further include compositions represented by the formula: M = M' or Sn, where m is a formal valence of 0<1≦m and M=M' or Sn, where M' is a non-tin metal of groups 2-16 of the periodic table. In general, organotin photoresists exhibit both high resolution and high etch resistance, allowing for the formation of small features and patterns. In situ hydrolysis during the coating process or after the coating step can be used to hydrolyze the hydrolyzable MX bonds to form oxo / hydroxo networks in the coating prior to patterning. The precursor compounds can form clusters in solution with appropriate ligand rearrangement. In this case, at least a portion of the hydrolyzable ligands may be substituted with an oxo bridge or hydroxyl group, such as three tin atoms, as described in U.S. Patent Application Publication No. 2019 / 0053001, entitled "Organotin Clusters, Solutions of organotin Clusters, and Application to High Resolution Patterning," Cardineau et al., and U.S. Patent Application Publication No. 2019 / 0308998, entitled "Tin Dodecamers and Radiation Pattenable Coatings With Strong EUV Absorption," Cardineau et al., both of which are incorporated herein by reference.

[0017] Formation of the photosensitive organotin coating can be accomplished through a variety of means known to those skilled in the art, such as spin coating. For solution deposition of the precursor, for the tin-based resists described above, the tin concentration is generally in the range of about 1 mM to about 1M, in yet another embodiment about 2 mM to about 750 mM, and in other embodiments about 5 mM to about 500 mM, in terms of the amount of tin. In some embodiments, the photosensitive organotin coating can be formed through vapor deposition techniques, such as atomic layer deposition (ALD) or chemical vapor deposition (CVD) techniques, as described in U.S. Pat. No. 10,228,618 B2 to Meyers et al., entitled "Organotin Oxide Hydroxide Patterning Compositions, Precursors, and Patterning," and U.S. Pat. No. 9,996,004 B2 to Smith et al., entitled "EUV Photopatterning of Vapor-Deposited Metal Oxide-Containing Hardmasks," respectively, both of which are incorporated herein by reference.

[0018] The thickness of the coating may generally depend on the precursor solution concentration, viscosity, and spin speed. For other coating processes such as vapor deposition, the thickness can generally be adjusted by selecting the coating parameters. In some embodiments, it may be desirable to use plating, which promotes the formation of small, high-resolution features. In some embodiments, the average dry thickness of the coating material before development may be about 1 micron or less, in yet other embodiments about 250 nanometers (nm) or less, in additional embodiments about 1 nanometer (nm) to about 50 nm, in other embodiments about 1 nm to about 40 nm, and in some embodiments about 1 nm to about 25 nm. The range of coating thickness after development of the exposed areas generally falls within the same ranges presented above, such that development removes a relatively small amount of exposed material. One of ordinary skill in the art will recognize that other ranges of solution concentrations and thicknesses within the explicit ranges above are contemplated and are within the scope of the present disclosure. The thicknesses can be evaluated using non-contact methods such as X-ray reflectance of the film and / or ellipsometry based on the optical properties of the film.

[0019] After deposition and formation of the organo-tin coating, an edge bead removal (EBR) cleaning step is commonly used. EBR processing is typically performed after photoresist deposition and before any heat treatment or bake, and involves removing the photoresist in selected areas by rinsing the periphery of the wafer or substrate with a solvent. EBR and backside cleaning involves applying an edge bead cleaning solution to the edge and backside of the wafer, as described in U.S. Pat. No. 10,627,719 to Waller et al., entitled "Methods of Reducing Metal Residue in Edge Bead Region from Metal-Containing Resists," which is incorporated herein by reference.

[0020] A soft bake, or post-apply bake (PAB), is typically performed prior to radiation exposure to hydrolyze hydrolyzable bonds in the precursor composition and / or drive off further solvent and promote densification of the coating material. In some embodiments, the PAB may be performed at a temperature of about 25° C. to about 250° C., in additional embodiments about 50° C. to about 200° C., and in yet other embodiments about 80° C. to about 150° C. The post-exposure bake may typically be performed for at least about 0.1 minutes, in yet other embodiments about 0.5 minutes to about 30 minutes, and in other embodiments about 0.75 minutes to about 10 minutes. Those of skill in the art will recognize that other ranges of PEB temperatures and times within the explicit ranges above are contemplated and are within the scope of the present disclosure. The coated materials generally comprise polymeric metal oxo-hydroxo networks based on the attachment of oxo-hydroxo ligands to metals that also bear alkyl ligands, or molecular solids consisting of polynuclear metal oxo-hydroxo species bearing alkyl ligands.

[0021] Generally, organotin photoresist coatings can be patterned using radiation. Suitable radiation sources include extreme ultraviolet (EUV), ultraviolet (UV), or electron beam (EB) radiation. In semiconductor device manufacturing, EUV radiation is generally preferred for its higher resolution compared to UV radiation and higher throughput compared to EB-based processes. The radiation can generally be directed at the substrate material through a mask and can be controllably scanned across the substrate to form a latent image in the resist coating.

[0022] According to the international standard ISO 21348 (2007), which is incorporated herein by reference, ultraviolet light spans wavelengths between 100 nm and less than 400 nm. Krypton fluoride lasers can be used as sources of 248 nm ultraviolet light. The ultraviolet range can be further subdivided in several ways under accepted standards, such as extreme ultraviolet (EUV) from 10 nm to less than 121 nm, and far ultraviolet (FUV) from 122 nm to less than 200 nm. The 193 nm line from an argon fluoride laser can be used as a radiation source in the FUV. EUV light is used for lithography at 13.5 nm, and the light is generated from high energy lasers or Xe or Sn plasma sources excited using discharge pulses. Commercial sources of EUV photons include scanners manufactured by ASML Holding NVNetherland. Soft x-rays can be defined as 0.1 nm to less than 10 nm. Light is directed through the mask to create a latent image in the radiation sensitive coating that includes exposed and unexposed areas.

[0023] The amount of electromagnetic radiation can be characterized by a fluence or a dose, which is obtained by integrating the radiative flux over the exposure time. In some embodiments, a suitable radiation fluence is about 1 mJ / cm. 2 ~about 200mJ / cm 2 and in yet another embodiment about 2 mJ / cm 2 ~Approx. 150mJ / cm 2 and in yet another embodiment about 3 mJ / cm 2 ~about 100mJ / cm 2 In one embodiment, the EUV radiation is about 150 mJ / cm 2 or approximately 2 mC / cm at 30 kV. 2 or approximately 2mC / cm 2 This can be done with the following doses of electron beam: A person of ordinary skill in the art will recognize that additional ranges of radiation fluence within the explicit ranges above are contemplated and are within the present disclosure.

[0024] In electron beam lithography, the electron beam typically induces secondary electrons that generally modify the irradiated material. Resolution can be at least in part a function of the range of the secondary electrons within the material, with high resolution generally believed to result from the short range of the secondary electrons. Based on the high resolution achievable by electron lithography using the organometallic coating materials described herein, the range of the secondary electrons within the organometallic material is limited. The electron beam can be characterized by the energy of the beam, with suitable energies ranging from about 5 eV to about 200 keV, and in yet other embodiments, from about 7.5 eV to about 100 keV. At 30 keV, the proximity effect corrected beam dose is about 0.1 microcoulombs per square centimeter (μC / cm). 2 ) ~ Approximately 5 millicoulombs per square centimeter (mC / cm 2 ), and in yet another embodiment, about 0.5 μC / cm 2 ~about 1mC / cm 2 and in other embodiments, about 1 μC / cm 2 ~about 100μC / cm 2 One of ordinary skill in the art would be able to calculate corresponding doses at other beam energies based on the teachings herein, and one of ordinary skill in the art will recognize that other ranges of electron beam properties within the explicit ranges above are contemplated and are within the scope of the present disclosure.

[0025] Following exposure to radiation and formation of the latent image, a post-exposure bake (PEB) is typically then performed. In some embodiments, the PEB may be performed at a temperature of about 45° C. to about 250° C., in additional embodiments, about 50° C. to about 190° C., and in yet other embodiments, about 60° C. to about 175° C. The post-exposure bake may generally be performed for at least about 0.1 minutes, in yet other embodiments, about 0.5 minutes to about 30 minutes, and in other embodiments, about 0.75 minutes to about 10 minutes. One of ordinary skill in the art will recognize that other ranges of PEB temperatures and times within the explicit ranges above are contemplated and are within the scope of the present disclosure. The PEB may also be designed to further strengthen the exposed areas without decomposing the unexposed areas to metal oxides.

[0026] It has been shown that both positive and negative tone patterning can be achieved in organotin oxide hydroxide systems by the composition containing metal oxide and organic ligand. For example, an organic solvent can be used as a developer, and then the unexposed material is dissolved and removed, leaving the exposed material, to achieve negative tone patterning. In contrast, an acidic or basic aqueous solution, such as an aqueous solution containing tetraalkylammonium hydroxide, can be used as a developer, and then the exposed material is dissolved and removed, leaving the unexposed material, to achieve positive tone patterning. The improved developer described herein is directed to negative tone imaging.

[0027] For negative imaging, the developer may include an organic solvent such as the solvent used to form the precursor solution. Additives may be added to the base organic solvent to form an improved developer. The additives may be other organic solvents, and the physical properties of the developer components are described to identify and distinguish them from other components. When developed to characterize the physical properties of the solvent, effective additives have been found to be compositions with specific values ​​of Hansen Solubility Parameters (HSP). The Hansen Solubility Parameters are δD (dispersion term), δP (polarity term), δH (hydrogen bonding term), and δT (total, (δT) 2 =(δD) 2+(δP) 2 +(δH 2 )). In the literature, either "δ" or "d" are used interchangeably to denote the Hansen solubility parameter, and the provisional application on which the priority claim is based used the "d" representation. The value of the Hansen solubility parameter was first proposed in Charles M. Hansen's doctoral dissertation in 1967 and has since been widely discussed in the technical literature. Generally, the Hansen solubility parameter for a composition is determined empirically, and the values ​​presented herein are taken from Knovel Solvents - A Property Database ((2008,2012) Author(s) / Editor(s): Wypych, George, Publisher: ChemTec Publishing Copyright Date 2008;2012;2019 ISBNN / AElectronic ISBN978-1-59124-533-9), which is incorporated herein by reference.

[0028] Without wishing to be limited by any hypothesis, it is believed that compositions with higher δH and / or δP parameters compared to solvents such as 2-heptanone will better dissolve partially hydrolyzed and / or condensed materials suspected of containing certain patterned defects such as micro-bridging and / or scum between features. As described below, the selection of base solvents can be generalized around 2-heptanone, and additives can be more efficiently identified by the relatively higher total values ​​of δH and δP. The enhanced developer effect of the blend of compositions may also be due to chemical interactions, i.e., complexation and / or coordination, of at least a portion of the developer or wash composition with the organotin material. In general, it is expected that developer compositions with higher δH and δP parameters than 2-heptanone will achieve improved results, i.e., lower defect density. Selection of the solvent blend allows control of the strength of the developer to produce the desired features at a reasonable dose. The base solvent may be selected to efficiently dissolve the unexposed patterning composition. The additive solvent can increase the strength of the developer, thereby helping to dissolve partially exposed or partially condensed patterning composition that may be present along the edges of the pattern or in random locations in the pattern, resulting in sharper edges (i.e., edges with less edge roughness).

[0029] In general, the selection of an appropriate developer solvent composition can affect the solubility parameters for both irradiated and unirradiated coating materials. Similarly, it can affect the volatility, flammability, toxicity, viscosity, and potential chemical interactions with other process materials of the developer. In particular, suitable base solvents for developers include, for example, aromatics (e.g., benzene, xylene, toluene), esters (e.g., propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate, n-butyl acetate, butyrolactone), ketones (e.g., methyl ethyl ketone, acetone, 2-butanone, cyclohexanone, 2-heptanone, 2-octanone), ethers (e.g., tetrahydrofuran, dioxane, anisole), 4-methyl-2-pentanol (and other weakly polar alcohols), and blends thereof. In general, base solvents have a solubility of about 16.0 (J / cm 3 ) 1 / 2 It has a total Hansen solubility parameter δH+δP of: Also, while suitable solvents are generally specified in terms of the chemical genera identified above, it should be noted that all members of these groups may have the specified solubility properties (especially when they contain multiple functional groups). In some contexts, solvent blends may be conveniently characterized by the chemical species and their functional groups without reference to solubility parameters.

[0030] For embodiments using a blend of solvents, the developer generally contains at least about 55% by volume of base solvent, and in further embodiments, about 60% to about 99.75% by volume, in additional embodiments, about 65% to about 99.5% by volume, in additional embodiments, about 70% to about 99.25% by volume, and in other embodiments, about 75% to about 99% by volume of base solvent, and may include one or more solvates having selected solubility parameters. One of ordinary skill in the art will recognize that other ranges of base solvent concentrations within the explicit ranges above are contemplated and are within the scope of the present disclosure. Volume percent values ​​are calculated based on the solvent volume prior to blending. Volume percent values ​​can be converted to weight percent values ​​depending on density, if desired.

[0031] As described herein, one or more additional highly polar solvents, referred to as polar solvents, may be added to the solvent blend to form an improved developer. In some embodiments, the developer may have from 0.25% to about 45% by volume of polar solvent, from about 0.4% to about 30% by volume in further embodiments, from about 0.5% to about 25% by volume in additional embodiments, and from about 0.75% to about 22% by volume of polar solvent in other embodiments. In some embodiments, the polar solvent has a polarity of at least about 16.0 (J / cm 3 ) 1 / 2The total Hansen solubility parameter δH+δP may be δH+δP. Suitable polar solvents include, for example, water, acetone, polar monohydroxyl alcohols (such as methanol, ethanol, propanol, isobutanol, pentanol, and mixtures thereof), polyhydroxyl compounds (such as ethylene glycol, propylene glycol, glycerol, and the like), pyrrolidones (such as 2-pyrrolidone, 1-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, and the like), glycol ethers (such as ethylene glycol monomethyl ether, and the like), carboxylic acids (such as formic acid, acetic acid, oxalic acid, 2-ethylhexanoic acid, and the like), diols (e.g., 1,2-hexanediol, 1,2-propanediol, 1,3-propanediol), and mixtures thereof. A person of ordinary skill in the art will recognize that other ranges of polar solvent concentrations within the explicit ranges above are contemplated and are within the scope of the present disclosure.

[0032] Water may be present in the initial solvent, and this inherent moisture should be considered in assessing water content. For convenience in distinguishing developers with potentially significant contributions from water, developers may be classified as having at least 0.1% by weight (1000 ppm) water, or having less than 0.1% by weight (1000 ppm), which may be conveniently referred to herein as having water, or being free or substantially free of water, respectively. For water, weight percent can be converted to volume percent depending on density, allowing for calculation of the volume percent of water consistent with the general description herein. Unless otherwise noted, ppm herein refers to parts per million by weight. In some embodiments, water is used alone, in small amounts, as an additive in the base solvent. Thus, in these embodiments, the developer has at least about 2000 ppm water, and in yet other embodiments, about 2500 ppm to about 10% by weight, in some embodiments, about 3500 ppm to about 5% by weight, and in other embodiments, about 4000 ppm to about 3% by weight water. A person of ordinary skill in the art will recognize that additional ranges of compositions within the explicit ranges above are contemplated and are within the present disclosure.

[0033] In addition to the primary developer solvent composition, the developer may contain additional compositions to facilitate the development process. Suitable additives include, for example, dissolved salts with cations selected from the group consisting of ammonium, d-block metal cations (e.g., hafnium, zirconium, lanthanum, etc.), f-block metal cations (e.g., cerium, lutetium, etc.), p-block metal cations (e.g., aluminum, tin, etc.), alkali metals (e.g., lithium, sodium, potassium, etc.), and combinations thereof, and dissolved salts with anions selected from the group consisting of fluoride ions, chloride ions, bromide ions, iodide ions, nitrates, sulfates, phosphates, silicates, borates, peroxides, butoxides, formates, ethylenediaminetetraacetic acid (EDTA), tungstates, molybdates, and combinations thereof. Surfactants may be added to reduce surface tension to facilitate application of the developer. Suitable surfactants may include, for example, ionic surfactants (such as alkyl ether sulfates, benzyl sulfonates, and phosphate esters) and nonionic surfactants (such as ethoxylated and alkoxylated fatty acids, ethoxylated amines, ethoxylated alcohols, alkyl and nonylphenol ethoxylates, etc.). Other suitable optional additives include, for example, phase transfer agents (such as tetraalkylammonium salts, polyethylene glycols, and crown ethers). When optional additives are present, the developer may include up to about 5% by weight of the additive, in yet another embodiment up to about 2.5% by weight of the additive, and in additional embodiments up to about 1% by weight of the additive. Those skilled in the art will recognize that other ranges of concentrations within the above explicit ranges are contemplated and are within the scope of the present disclosure. Additives may be selected to improve contrast, sensitivity, and linewidth roughness. Additives in the developer may also inhibit the formation and precipitation of metal oxide particles.

[0034] The developer can be applied to the patterned coating material using any reasonable approach. For example, the developer can be sprayed onto the patterned coating material, or the structure can be dipped or immersed in the developer. Spin coating can also be used. For automated processing, a puddle method can be used, which involves pouring the developer onto the coating material in a fixed format. If desired, spin rinsing and / or drying can be used to complete the development process. After the image is developed, the coating material is disposed on the substrate as a pattern.

[0035] Development can be performed using any reasonable process approach, such as spray coating, puddle dipping, etc. For commercial production, development is typically adapted to the process equipment provided. Development can be performed for about 2 seconds to about 30 minutes, in yet another embodiment, for about 3 seconds to about 15 minutes, in other embodiments, for about 4 seconds to about 10 minutes, and in additional embodiments, for about 5 seconds to about 5 minutes. One of ordinary skill in the art will recognize that other ranges within the explicit ranges above are contemplated and are within the scope of the present disclosure.

[0036] Depending on the design of the coating material, a high contrast in material properties can be produced between the irradiated areas with condensed coating material and the non-irradiated areas of the coating material with substantially intact photosensitive ligands, such as organic and / or carboxylate ligands, which further facilitates the formation of high resolution lines with smooth edges after development, as described in the examples.

[0037] After completion of the development step, including optional rinsing, the coating material may be heat treated to further condense the material and to further dehydrate, densify, or remove residual developer from the material. This heat treatment may be particularly desirable for embodiments in which the oxide coating material is incorporated into a final device. However, it may be desirable to perform a heat treatment for some embodiments in which the coating material is used as a resist and is ultimately removed, if stabilization of the coating material is desired to further facilitate patterning. In particular, baking of the patterned coating material may be performed under conditions that provide the desired level of etch selectivity for the patterned coating material. In some embodiments, the patterned coating material may be heated at a temperature of about 100° C. to about 600° C., in yet other embodiments, about 175° C. to about 500° C., and in additional embodiments, about 200° C. to about 400° C. Heating may be performed for at least about 1 minute, in other embodiments, about 2 minutes to about 1 hour, and in still other embodiments, about 2.5 minutes to about 25 minutes. Heating can be performed in air, vacuum, or in an inert gas atmosphere such as Ar or N2. One of ordinary skill in the art will recognize that other ranges of temperatures and times for thermal treatment within the explicit ranges above are contemplated and are within the scope of the present disclosure. Similarly, non-thermal treatments such as blanket UV exposure or exposure to an oxidizing plasma such as O2 may also be used for similar purposes.

[0038] In some embodiments, the average pitch (half pitch) of adjacent linear segments of adjacent structures may be about 60 nm or less (30 nm half pitch), in some embodiments, about 50 nm or less (25 nm half pitch), and in yet other embodiments, about 34 nm or less (17 nm half pitch). Pitch can be evaluated by design and can be confirmed using scanning electron microscopy (SEM), such as top-down imaging. As used herein, pitch refers to the spatial period, or center-to-center distance, of repeating structural elements, and as commonly used in the art, half pitch is half the pitch. Dimensions of features of a pattern may also be described in terms of the average width of the feature, and are generally evaluated away from corners, etc. Features may also refer to gaps between material elements and / or material elements. In some embodiments, the average width may be about 25 nm or less, in yet other embodiments, about 20 nm or less, and in additional embodiments, about 15 nm or less. A person of ordinary skill in the art will recognize that other ranges of pitch and average width within the explicit ranges above are contemplated and are within the scope of the present disclosure. Based on these processes, patterning can be adapted to form various devices, such as electronic integrated circuits, and the patterning process can generally be repeated to appropriately form layered structures, such as transistors and other components.

[0039] Wafer throughput is a substantial limiting factor in the implementation of EUV lithography in high volume semiconductor manufacturing and is directly related to the dose required to pattern a given feature. However, while chemical strategies exist to reduce the imaging dose, for EUV photoresists with feature sizes and pitches below 50 nm, there is generally a negative correlation between the imaging dose required to print a target feature and the feature size uniformity (e.g., LWR), thereby limiting the final device operability and wafer yield. Photoresist sensitivity can be expressed using dose-to-gel values, and imaging dose requirements can be evaluated by forming an array of exposed pads with varying exposure doses, with exposure times graded from pad to pad. The film can then be developed, and the remaining resist thickness can be evaluated for all pads, for example, using spectroscopic ellipsometry. The measured thickness can be normalized to the maximum measured resist thickness and plotted against the logarithm of the exposure dose to form a characteristic curve. The maximum slope of the normalized thickness vs. log dose curve is defined as the photoresist contrast (γ), and the dose value at which a tangent line drawn through this point is equal to 1 is defined as the photoresist dose vs. gel (D g ) Thus, common parameters used for photoresist characterization may be approximated according to Mack, C. Fundamental Principles of Optical Lithography, John Wiley & Sons, Chichester, UK; pp 271-272, 2007.

[0040] In some embodiments, the average linewidth roughness may be about 5.5 nm or less, in some embodiments, about 5 nm or less, and in yet other embodiments, about 4.5 nm or less. As shown in the examples, the linewidth roughness can be evaluated as a function of the critical dimension. The linewidth roughness is evaluated by analyzing the top-down SEM images to derive the 3σ deviation from the average linewidth. The average value includes both high frequency and low frequency roughness, i.e., short correlation length and long correlation length, respectively. The linewidth roughness of organic resists can be characterized primarily by the long correlation length, but the organometallic coating materials of the present application exhibit significantly shorter correlation lengths. In the pattern transfer process, the short correlation roughness can be smoothed out during the etching process to produce higher fidelity patterns. Those skilled in the art will recognize that other ranges of linewidth roughness within the above explicit ranges are also contemplated and their thicknesses are within the scope of the present disclosure. Based on these processes, patterning can be adapted to form various devices, such as electronic integrated circuits, and generally layered structures, such as transistors and other components, can be appropriately formed by repeating the patterning process.

[0041] In some embodiments, it may be beneficial to perform an additional washing process immediately after the development process. The washing process generally involves contacting the developed material with a solvent or an additional composition including a solvent and an additive. As shown in the examples, a washing step using only a solvent tends to increase the number of defects. However, a washing step using the improved development composition described above results in fewer defects and / or a higher uniformity of the process results. In some embodiments, the washing composition may be one of the same compositions as described above as the developer. For example, the washing composition may include a solvent selected from ketones, esters, ethers, or mixtures thereof, and the additive may include carboxylic acids, monohydroxyl alcohols, polyols such as diols, pyrrolidones, lactones, or mixtures thereof. Specifically, for example, the washing composition may include a mixture of 2-heptanone and 1,2-hexanediol. In general, the washing process may be similar to the development process, except that the development step results in a large amount of removal of the coating, whereas the washing step generally does not remove a large amount of material. The washing process may occur for between 1 second and about 20 minutes, and in yet another embodiment for between about 2 seconds and about 12 minutes, and in additional embodiments for between about 4 seconds and about 6 minutes. A person of ordinary skill in the art will recognize that other ranges within the explicit ranges above are contemplated and are within the present disclosure.

[0042] Another cleaning approach has been described by the applicant in U.S. Patent Application Serial No. 16 / 654,080 to Kocsis et al., entitled "Patterned Organometallic Photoresists and Methods of Patterning," which is incorporated herein by reference. The cleaning in the '080 application was based on an aqueous cleaning agent, which tended to dissolve the exposed portions of the pattern to some extent. However, the cleaning process was controlled to limit this dissolution of the exposed portions of the pattern. This cleaning was effective in removing defects and also altered the dimensions of the pattern. Such a process may be considered as an alternative to the improved development process of the present application. In the cleaning described in the examples, the cleaning step using only a base solvent generally results in an increase in defects. The cleaning using the improved developer resulted in some additional reduction in defects.

[0043] The processing approach of this application is designed to reduce or eliminate defects such as micro-bridging defects and larger defects. To make the data comparison uniform, bridging defects, particle defects, and coarse cluster defects are not considered in the evaluation of micro-bridging defects. Bridging differs from micro-bridging in that bridging is determined by a critical number of pixels in the y-direction (if it exceeds a size threshold, it is considered a bridge and is rejected). In most, but not all, cases, manual review of these images suggests another mechanism, such as falling type particles. Compared to the number of micro-bridges, these have a relatively small contribution to the total defect count (less than 10% for high defect samples such as control wafers). An automated process can be used to evaluate the micro-defects as described in the examples below. Essentially, a series of critical dimension scanning electron micrographs are taken. The CD-SEM images can be analyzed by counting the number of micro-bridges using analysis software. An example of a micro-bridge is shown in the SEM micrograph in FIG. 1.

[0044] To aid in the evaluation of development, wafers were patterned and the patterning was evaluated as a function of EUV dose. To begin with, imaging is viewed as a step function of illuminated and unilluminated areas. For patterning of very fine features such as lines and spaces, and to aid in the development of achieving low feature roughness, the actual feature width and pitch for a given dose were evaluated to evaluate the EUV dose. size Determine. E size can be defined as the dose to obtain a target feature width with a mask designed to achieve said feature width with a selected developer. A stronger developer will etch more along the edge for a particular exposure dose, and correspondingly a weaker developer will etch less along the edge, such that the developed linewidth depends on the developer. The wafer is exposed across a range of EUV doses, producing a grid of fields of nominally identical features, but each irradiated with a different EUV dose, resulting in correspondingly different feature sizes. The dose that achieves the target linewidth is called E size and the corresponding unit of dose (mJ / cm 2 ) E size Values ​​of are presented in the examples to evaluate developer performance at specific processing conditions.

[0045] Generally, it is desirable to lower the EUV dose to improve the throughput of the EUV scanning components, since the number of exposures may be dose dependent. However, the trade-off between patterning dose and feature roughness and / or final resolution is well known, and pattern quality is generally improved by increasing the dose. As seen in the examples below, the developers, processing conditions, and related methods described herein can provide a larger process window, i.e., the range of doses that provide sufficiently low LWR and / or low defects, than conventional ketone developers. Furthermore, the present invention allows the selection of specific processing conditions and developer compositions to reduce LWR and / or patterned defects without the associated increase in dose. The patterning composition itself is designed to have low dose requirements. Thus, the improved patterning compositions and methods used herein allow for excellent pattern quality at reasonable dose values.

[0046] After patterning, the patterned material can be used for further processing such as deposition into the gaps in the patterned material and / or etching to remove substrate material between the gaps in the patterned material. The patterned resist material can then be removed after further treatment with a suitable etchant composition such as dilute base or BCl3 plasma. The above process can be repeated multiple times to form a stack of patterned layers to form functional components.

[0047] In the following examples, data is presented that demonstrates the improved performance of the compositions of the present invention.The effectiveness of the compositions of the present disclosure was examined using a representative organotin photoresist composition as described in U.S. Patent No. 10,228,618 B2 to Meyers et al., which is incorporated herein by reference.The performance of the present invention was shown to be improved over standard ketone solvent developer compositions.The newly discovered developer allows the formation of patterns and structures with improved density of patterned defects, especially microbridging defects, at comparable dimensions. EXAMPLES

[0048] Example 1. Pattern formation using various developer compositions This example presents dose vs. gel values ​​obtained by exposing an organotin oxide hydroxide photoresist to EUV radiation and developing in organic solvents with different Hansen Solubility Parameters.

[0049] Separately prepared solutions t BuSn(NEt2)3 and Sn(NMe2)4 were combined in dry 4-methyl-2-pentanol to prepare a 0.04M solution as described in Example 4 of the '618 patent cited above. t Tert-butyltin oxide hydroxide photoresist films were deposited from precursor coating solutions prepared by mixing BuSn(NEt2)3 and 0.01M Sn(NMe2)4, resulting in a final solution containing 0.01M Sn(NMe2)4. Thin films for EUV contrast curves were deposited on silicon wafers (100 mm diameter) with native oxide surfaces. The Si wafers were treated with hexamethyldisilazane (HMDS) vapor prime prior to deposition. The precursor coating solutions were spin-coated on the Si substrates at 1000 rpm in air and baked at 100 °C for 2 min on a hotplate in air to remove residual solvent and volatile hydrolysis products. The film thickness after coating and baking was measured by ellipsometry to be about 25 nm.

[0050] A linear array of 50 circular pads, each about 500 μm in diameter, was exposed to EUV light on each wafer using the Lawrence Berkeley National Laboratory Micro Exposure Tool. The pad exposure time was set to 0.63 mJ cm2, delivering an EUV dose to each pad. -2 to 27.39 mJ cm -2The exposure was adjusted to step in exponential 8% steps from 0.1 to 1.0 mm. After exposure, the wafers were subjected to a post-exposure bake (PEB) at 160°C on a hot plate in air for 2 minutes. The exposed film was then dipped in one of the developer solvents listed in Table 1 for 30 seconds to produce a negative tone image, i.e., the unexposed portions of the coating were removed. The film was removed from the developer solvent and dried with a nitrogen gun. A final 5 minute hot plate bake at 150°C in air was performed after development. The residual thickness of the exposed pads was measured using a JAWoollam M-2000 spectroscopic ellipsometer. The measured thickness for each pad was then normalized to the maximum measured resist thickness and plotted against the log of the exposure dose to form a characteristic curve for each developer solvent. The maximum slope of the normalized thickness vs. log dose curve was defined as the photoresist contrast (γ) and occurs at a dose value D1. The photoresist dose vs. gel (D g ) is defined as the dose at which the tangent of the slope γ drawn through D1 is equal to 1. Thus, common parameters used for photoresist characterization may be approximated according to Mack, C. Fundamental Principles of Optical Lithography, John Wiley & Sons, Chichester, UK; pp 271-272, 2007.

[0051] D g The practical interpretation of D is the dose required to achieve the maximum development rate change relative to unexposed material. D for identical organotin oxide hydroxide photoresist films developed in each solvent in Table 1 g The values ​​are plotted against the sum of the polar terms for each solvent, defined as the sum of the Hansen δP and δH parameters in Figure 2. Hansen solubility parameters were taken from Wypych, G. Knovel Solvent Database, ChemTec Publishing, 2008, 2012. D gThere is a clear positive correlation between the polarity and the sum of the polarity terms. Thus, more polar developer solvents are generally stronger developers, leading to a higher D for a given resist and process. g Leads to...

[0052] [Table 1]

[0053] Example 2. Preparation of organotin coated resist and evaluation of patterning performance In this example, the developer composition comprises: t Prepared by in situ hydrolysis of a precursor solution containing BuSnX3 and MeSnX3 compounds. t BuSnO (3 / 2-((x / 2)) (OH) x and MeSnO (3 / 2-(X / 2)) (OH) x and evaluation of these films is generally described to provide a context for the results of the examples below.

[0054] The photoresist precursor coating solution was prepared using a method similar to that described in U.S. Patent Application Publication No. 2019 / 0391486 by Jiang et al. t amyl)3 and 80 mol% t BuSn(O t Amyl)3(O t A mixture containing tin (amyl = 2-methylbutane-2-oxide) was prepared under an inert gas atmosphere and then dissolved in 4-methyl-2-pentanol with a pre-adjusted H2O concentration of approximately 300 ppm. The final Sn concentration of the precursor coating solution was 0.05 M.

[0055] A flow diagram of the procedure for the analysis of wafer patterning defects is shown in Figure 3. The precursor solutions mentioned above were used to coat organotin oxide hydroxide photoresist films using a TEL CLEAN TRACK LITHIUS Pro Z coater / developer. Silicon wafers (300 mm diameter) were coated with a 10 nm spin-on glass (SOG) underlayer (ISX328, JSR) and baked at 220°C for 1 min in air prior to photoresist coating. A solvent pre-wet step using a PGME / PGMEA mixture was used to improve the photoresist coat uniformity. The resist precursor coating solution was then spin-coated at 1394 rpm in air onto the underlayer-coated substrate. After edge bead cleaning (EBR) and backside cleaning, the coated wafer was post-apply baked (PAB) at 100°C for 1 min on a hotplate in air. Edge bead washing is generally described in U.S. Patent Application Publication No. 2018 / 0046086 to Waller et al., entitled "Methods of Reducing Metal Residue in Edge Bead Region From Metal-Containing Resists," which is incorporated herein by reference.

[0056] After PAB, the resist-coated substrates were exposed to extreme ultraviolet radiation using an ASML NXE:3300B scanner with 90x dipole illumination with a numerical aperture of 0.33. A pattern of equal vertical 16 nm lines and spaces (16p32) was projected onto the coated wafer with a fixed focus, and after each exposure the wafer was stepped to create an approximately circular field array centered on the center of the wafer at various exposure doses. The exposed resist film and substrate were then returned to the coater / developer track and subjected to a 1 minute hotplate PEB in air at the specified temperature. After PEB, the exposed film was then developed with a selected developer composition using a set paddle development recipe for 15 seconds, followed by a dynamic rinse with a cleaning solution for an additional 10 seconds to produce a negative tone image, i.e., the unexposed portions of the coating were removed. A final 1 minute hotplate bake in air at 150°C was performed after development.

[0057] A Hitachi CG5000 CD-SEM was used to measure the average line width (critical dimension, CD) and 3 sigma line width roughness (LWR) of each field along the scanned dose range. From these data, dose vs. size (E size , i.e., the dose required to print a line CD equal to one half pitch) and four fields spanning the target CD selected for microbridging defect analysis were calculated.

[0058] Microbridging defect analysis was performed by collecting 150 CD-SEM images from the same single location in the four selected line-space fields for each wafer. Images were collected at approximately 164,000x magnification, 0.823 μm×0.823 μm field of view, TV scan, accelerating voltage of 800 V, and beam current of 8 pA. Sixteen frames were averaged per image. Each set of 150 images was analyzed using Stochalis image analysis software (developed at and distributed by Interuniversity Microelectronics Centre, Belgium) (operated in “Space” mode with the following parameter settings: SumLines=4, Smoothing=7; CD_Threshold=61; DThres_nok_Space=90; and Lnok_min_Space=4) and the total number of microbridging defects detected per field was tabulated. EUV image analysis is further described in P. De Bisschop and E. Hendrickx, "Stochastic effects in EUV lithography," Proc. SPIE 10583, Extreme Ultraviolet (EUV) Lithography IX, 105831K (19 March 2018); https: / / doi.org / 10.1117 / 12.2300541, which is incorporated herein by reference. Microbridge defect density at target CD (specified as 16nm or 18nm in each example) across the measurement range was estimated by fitting an exponential function to the defect density vs. CD curves generated from four data points per wafer, and reported as defects per 150 images or "Def / Die 16p32". The total sampling area per 150 images is approximately 101.6 square microns. The results for the developer containing formic acid additive are shown in Figures 5, 6 and 13, the results for the developer containing EHA additive are shown in Figures 8 and 9, the results for the developer with acetic acid additive are shown in Figure 15, the results for the developer with diol additive are shown in Figure 16, the developer with water as an additive is shown in Figure 17 and the results for the alcohol developer composition are shown in Figure 21.Figure 13 shows the defect density on 18p32 patterns for a developer containing a formic acid additive. Figure 15 shows the defect density on 18p32 patterns for a developer containing an acetic acid additive. Figure 18 shows the effect of washing conditions on defect density. The disclosed additives and processing conditions are generally shown to reduce the defect density of patterned organotin oxide hydroxide photoresists.

[0059] Example 3.2 - Heptanone and Formic Acid Developer Composition This example demonstrates the improved results obtained using a developer that uses a blend of 2-heptanone and formic acid, and shows a significant reduction in microbridging defects.

[0060] A conventional 2-heptanone developer composition (HF0) was used as a control developer and wash solvent.

[0061] A set of developer solutions was prepared by mixing 98% (w / w) pure formic acid with 2-heptanone at a concentration of either 2% by volume formic acid (Dl) or 10% by volume formic acid (D2). Prior to formulation, all glassware was washed three times with isopropyl alcohol and baked at 100 °C for 24 h. Preparation was performed in a fume hood. A known volume of 2-heptanone (EUVR Developer, TOK America, containing 100-300 ppm H2O) was dispensed into a glass bottle. The amount required to obtain the target volume percent of formic acid (obtained from EMD Millipore) was then added to the bottle via a graduated cylinder or autopipette, and the mixture was capped and placed on a shaker table to mix thoroughly.

[0062] The wafers were coated, exposed, developed, rinsed, and analyzed according to Example 2. The rinse solution was 2-heptanone. All samples were tested at post-exposure bake temperatures of 140°C, 160°C, and 180°C. Samples (D1) and (D2) were additionally tested at a post-exposure bake temperature of 120°C. The samples were then developed using either (HD0), (D1), or (D2). A final hotplate bake at 150°C in air for 60 seconds was performed after development.

[0063] If stock formic acid is assumed to contain 2% water by weight, then a 10% by volume formic acid developer contains about 3000 ppm water, and a 2% by volume formic acid developer contains about 600 ppm water. The partitioning effect of water in 2-heptanone solutions is investigated in Example 9, but the effect of water in these developer samples is significantly smaller than that of formic acid.

[0064] The developer composition (D2) was measured immediately after preparation and after one week. 1 H NMR analysis was performed and compared to the 2-heptanone control developer (HF0) of Example 2. See Figure 4. The NMR results suggest that the developer composition is stable over a one week time frame.

[0065] Figure 5 provides the microbridge density as a function of post-exposure bake temperature. For (D1) and (D2), a reduction in microbridge density was observed compared to the 2-heptanone control developer (HF0) at all tested PEB temperatures.

[0066] FIG. 6 provides the microbridge density as a function of equivalent dose density. It can be seen that the set PEB dose increases, but by shifting the process PEB temperature, the equivalent dose vs. size (E size ) can reduce the defect rate.

[0067] Figure 7 provides the line width roughness (LWR) in nanometers as a function of equivalent dose versus size. It can be seen that the dose at a given PEB increases, but by shifting the process PEB temperature, the equivalent dose density (mJ / cm 2 ) can be used to propose LWR.

[0068] Data from Figures 5-7 show that developer compositions with 2-10% (by volume) formic acid additive in 2-heptanone can reduce microbridging density in organotin resist patterns with 16 nm lines on 32 nm pitch compared to a 2-heptanone control developer composition. The reduction in microbridging density is roughly one order of magnitude and up to about two orders of magnitude at comparable dose densities, with a substantial dose penalty. Increasing additive concentration is shown to reduce microbridging density at a given PEB temperature or dose density. Increasing additive concentration is shown to reduce linewidth roughness roughly at a given dose density.

[0069] Example 4. 2-Heptanone and 2-Ethylhexanoic Acid (EHA) Developer Composition This example demonstrates the improved results obtained using a developer that uses a blend of 2-heptanone and ethylhexanoic acid, resulting in a significant reduction in microbridging defects.

[0070] A conventional 2-heptanone developer composition (HF0) was used as a control developer and wash solvent.

[0071] A set of developers was prepared by mixing neat ethylhexanoic acid (EHA) with 2-heptanone at a concentration of either 2% EHA by volume (D3) or 10% EHA by volume (D4). Prior to formulation, all glassware was washed three times with isopropyl alcohol and baked at 100°C for 24 hours. Preparation was performed in a fume hood. A known volume of 2-heptanone (EUVR Developer, TOK America, containing 100-300 ppm H2O) was dispensed into a glass bottle. The amount required to obtain the target volume % of EHA (Alfa Aesar) was then added to the bottle via a graduated cylinder or autopipette, and the mixture was capped and placed on a shaker table to mix thoroughly.

[0072] The wafers were coated, exposed, developed, washed, and analyzed according to Example 2. The washing solvent was 2-heptanone. All samples were tested at post-exposure bake temperatures of 140°C, 160°C, and 180°C. The samples were then developed using either (HD0), (D3), or (D4). A final 60 second hotplate bake at 150°C in air was performed after development.

[0073] Figure 8 provides the microbridge density at a target CD of 16 nm as a function of post-exposure bake temperature. For (D3) and (D4), a reduction in microbridge density was observed compared to the 2-heptanone control developer (HF0) at several tested PEB temperatures.

[0074] Figure 9 provides the micro-bridge density as a function of equivalent dose density for the control developers (HF0) and (D3) and (D4). It can be seen that the dose at a given PEB increases, but by shifting the process PEB temperature, the defect rate can be reduced at equivalent dose density.

[0075] Data from Figures 8-9 show that developer compositions with 2-10% (by volume) EHA additive in 2-heptanone can reduce microbridging density in organotin oxide hydroxide photoresist patterns with 16 nm lines on 32 nm pitch compared to the 2-heptanone control developer composition. A clear reduction in microbridging density can be seen for the EHA-containing developers at post-exposure bake temperatures of 160°C and 180°C. In Figure 7, the microbridging density at a PEB temperature of 180°C using developer (D4) is about one-third of the microbridging density seen with the control developer (HF0). Furthermore, a reduction in microbridging density is seen at a post-exposure bake temperature of 120°C for the more EHA-concentrated developer (D4) (10% EHA by volume). Figure 8 shows that increasing the concentration of the additive from 2% by volume to 10% by volume reduced the microbridging density at a given dose density. Increasing the concentration of additives generally correlates with a decrease in defect density; however, the results show that the performance of the developer is sensitive to PEB temperature and dose density compared to the control developer. 2 At 1000 rpm, the 2% EHA by volume did not perform better than the control developer. The positive effect of the EHA additive is particularly evident at lower dose densities. For example, 2% EHA by volume showed a reduction in defects at dose densities of 30 mJ / cm compared to the control developer (HF0). 2 It is about 1.7 times higher.

[0076] Example 5. Organic Solvent and Carboxylic Acid Developer Compositions This example describes the preparation of developers consisting of 2-heptanone or PGMEA with formic acid or acetic acid as additives.

[0077] Prior to formulation, all glassware was washed three times with isopropyl alcohol and baked at 100 °C for 24 hours. Preparation was performed in a fume hood. Known volumes of solvent, i.e., 2-heptanone (EUVR developer, TOK America, containing 100-300 ppm H2O) or propylene glycol methyl ether acetate (PGMEA, Sigma Aldrich, 99.5%), were dispensed into glass bottles. The required amount to obtain the target volume percent of acetic acid (JTBaker, 99.5-100.5%) or formic acid (98-100%, EMD) was then added to the bottle via graduated cylinder or autopipette, and the mixture was capped and placed on a shaker table to mix thoroughly. The solutions listed in Table 2 were created by varying the ratio of additives to the total volume of added acid and added solvent.

[0078] [Table 2]

[0079] Examples 6 and 7 present performance data for the developer compositions in Table 2.

[0080] Example 6. Analysis of Microbridging from the Formic Acid-Containing Developer of Example 5 This example demonstrates the improved patterning performance obtained using formic acid as a developer additive. Organotin oxide hydroxide photoresist patterns are developed using a developer with blends of 2-heptanone or PGMEA with formic acid, prepared as shown in Example 5. The dose vs. size and LWR of 16p32 images were analyzed and the number of defects for the patterns in four fields was evaluated based on CD18nm as described in Example 2. Compared to the control developer, the developer with the formic acid additive generally showed improved performance, with a significant improvement with increasing line CD.

[0081] Line-space patterns on 32 nm pitch were formed by preparing and processing organotin oxide hydroxide photoresist precursor solutions and photoresist films as shown in Example 2. Developers HF0-HF4 and PF0-PF4 from Example 5 were used in the development step, and all wafers were rinsed for 10 seconds with the corresponding developer. All eight developers were tested on wafers PEB'd at 180°C, but only developers (HF0), (PF0), (HF2), and (PF2) were tested on wafers PEB'd at 140°C and 160°C.

[0082] Representative SEM pictures of the resulting 32 nm pitch patterns from the field with the average line CD closest to 16 nm are shown for each wafer in Figures 10 and 11. At comparable PEB temperatures, the developer with formic acid additive yielded roughly 1.2 times the E size It can be seen that the formic acid additive causes a decrease in LWR compared to the control solvent, which correlates with an increase in field dose comparable to that of the formic acid additive, and an increase in the volume % of formic acid in the developer. This trend is also visually evident, as patterns developed with solutions containing higher concentrations of formic acid additive show reduced incidence of scum and micro-bridging even in small areas sampled in a single image. As shown in Figure 11, during PEB at 180 °C, a developer containing undiluted PGMEA (PF0) is unable to consistently resolve the line-space pattern, with numerous particle, bridge, and scum defects clearly visible. However, when the formic acid additive is present in the same solvent, image fidelity is significantly improved at all additive amounts tested.

[0083] LWR values ​​for all fields with measurable line CD for all 12 wafers shown in Figure 10 are plotted in Figures 12A-12C as a function of CD for PEB temperatures of 140°C, 160°C, and 180°C, respectively. At low CDs (and associated low doses), all developers appear to have a similar effect on LWR for each PEB temperature, except for the control developer (PF0) as already mentioned. Compared to development with the control developers (PF0) and (HF0), a modest LWR reduction at constant CD is generally observed for (PF2) and (HF2). However, a strong divergence is observed as the line CD approaches 16 nm. The LWR of patterns developed with (PF0) and (HF0) begins to increase immediately, whereas the LWR of patterns developed with (PF2) and (HF2) continues to decrease gradually and eventually begins to increase when the CD exceeds about 18 nm. To the extent that the lithographic process window is constrained by LWR and edge placement errors, the larger line sizes that can be printed before this “LWR take-off” (as is the case for many advanced node applications) represents an extension of the effective processing of the photoresist when developed with the formic acid-containing developers disclosed herein.

[0084] The micro-bridging defect analysis method described in Example 2 was similarly applied to the 18 wafers mentioned above. A target CD of 18 nm was selected, and 150 SEM images were collected and analyzed for every 4 fields with CDs close to the target on each wafer. After image analysis, defect counting, and curve fitting, the number of defects per 150 images of the 18p32 pattern at each process condition was estimated. The logarithm of this number (base 10 logarithm) was calculated as E in FIG. sizeThe data are plotted against (at 16p32). The developer used per wafer is indicated on the data point label. At 180°C PEB conditions, a strong reduction in the number of micro-bridge defects (about 50x) is clearly seen even with the lowest volume % formic acid tested (PF1, HF1) compared to the control developers (PF0, HF0). The number of defects continues to decrease as the volume % of formic acid increases from (HF1) and (PF1) to (HF4) and (PF4). It can be seen that for all PEBs tested, the percentage reduction in defects is roughly similar (about 500x) for (HF2) and (PF2) compared to (HF0) and (PF0). Notably, this large reduction in defects at a constant PEB is a function of dose (E size ), but comparing the data points and trend lines at roughly equivalent dose conditions (i.e., HF0, 160° C. and HF1, 180° C. or HF0, 140° C. and HF2, 180° C.), developer additives can be used in parallel with other process conditions to significantly reduce defects at nominally equivalent doses.

[0085] Example 7. Analysis of Microbridging from the Acetic Acid-Containing Developer of Example 5 In this example, the improved patterning performance obtained using acetic acid as a developer additive is demonstrated. Organotin oxide hydroxide photoresist patterns are developed using a developer with a blend of PGMEA and acetic acid. A significant reduction in microbridging defects is demonstrated using high resolution imaging.

[0086] Line-space patterns on 32 nm pitch were formed by preparing and processing organotin oxide hydroxide photoresist precursor solutions and photoresist films as shown in Example 2. Developers PA1-PA5 were prepared by mixing acetic acid and PGMEA as described in Example 5. All wafers were washed with the corresponding developer. Each of the five developers was tested on wafers treated with PEB at 170°C, 180°C, and 190°C and compared with (PF0).

[0087] Representative SEM pictures of the resulting 32 nm pitch patterns from the field with the average line CD closest to 16 nm are presented for each wafer in FIG. 14. At comparable PEB temperatures, the developer with acetic acid additive yielded roughly size It can be seen that increasing the volume percent of acetic acid in the developer causes a comparable increase in field dose and a decrease in LWR compared to the control solvent that roughly correlates with increasing the volume percent of acetic acid in the developer.

[0088] The microbridging defect analysis method described in Example 2 was applied to the resulting line-space pattern using a target CD of 18 nm. size The logarithm of the fitted average defect count per 150 images for the 18p32 field of each wafer was plotted against (at 16p32). The developer used per wafer is indicated on the data point labels. A strong reduction (about 50-fold) in the number of micro-bridging defects is again seen for all PEB conditions, even at 1 vol.% acetic acid in PGMEA (PA1), compared to the control developer (PF0). As seen with formic acid, the number of defects continued to decrease as the vol.% of acetic acid was increased up to 10% (PA5). Similarly, comparing the data points and trend lines at roughly equivalent dose conditions (i.e., PF0, 170°C and PA1, 190°C), the acetic acid additive can be used in parallel with other process conditions to significantly reduce defects without a dose penalty.

[0089] Example 8.2 - Heptanone and Diol Developer Composition This example demonstrates the improved patterning performance obtained using diols as developer additives. Organotin oxide hydroxide photoresist patterns are developed using a developer containing blends of 2-heptanone and 1,6-hexanediol, 1,2-hexanediol, or 1,2-propanediol. A significant reduction in microbridging defects is demonstrated using high resolution imaging.

[0090] Prior to formulation of the developer, all glassware was washed three times with isopropyl alcohol and baked at 100°C for 24 hours. Preparation was performed in a fume hood. A 2% by weight solution of 1,6-hexanediol (HD1) was prepared by adding 10 g of 1,6-hexanediol (TCI) to a 500 mL volumetric flask containing approximately 400 mL of 2-heptanone (TOK). The flask was swirled until dissolution was complete, and then the total volume was diluted to 500 mL with additional 2-heptanone.

[0091] A known volume of 2-heptanone (EUVR Developer, TOK America, containing 100-300 ppm H2O) was dispensed into glass bottles. The amount needed to achieve the target volume percent diol additive was then added to the bottles via graduated cylinder or autopipette, and each solution was capped and placed on a shaker table to mix thoroughly.

[0092] A developer solution (HD2) was prepared by mixing 1,2-hexanediol (TCI, 96%) at 2% by volume in 2-heptanone.

[0093] A 10% by volume solution of 1,2-propanediol was prepared by mixing 450 mL of 2-heptanone (TOK) and 50 mL of 1,2-propanediol (Sigma-Aldrich) in a 500 mL Kimax bottle (HD3). After thorough combination, the solution was dispensed into two 240 mL amber glass bottles.

[0094] The wafers were coated, exposed, developed, washed and analyzed according to Example 2.

[0095] (HD1) Samples were tested at post-exposure bake temperatures of 120° C., 140° C., 160° C., and 180° C., and then developed with the prepared developer compositions and washed.

[0096] (HD2) Samples were tested at post-exposure bake temperatures of 120° C., 160° C., and 180° C., and then developed with the prepared developer compositions and washed.

[0097] (HD3) Samples were tested at post-exposure bake temperatures of 120° C., 140° C., 160° C., and 180° C., and then developed with the prepared developer compositions and washed.

[0098] A control water wafer sample was also prepared that was subjected to a post-exposure bake temperature of 160° C. and then developed in developer (HF0) and washed.

[0099] The microbridging defect analysis method described in Example 2 was applied to the resulting line-space patterns using a target CD of 16 nm. size The fitted defect counts per 150 images of the 16p32 field for each wafer are plotted against (at 16p32). The PEB temperature for each wafer is indicated by the data point labels. For wafers treated with a 160°C PEB, a clear reduction in defects is seen for developers containing diol additives, with developer (HD3) (2 vol.% 1,2-propanediol in 2-heptanone) showing the largest reduction (about 3-fold) versus (HD0). This trend continues across all PEB temperatures tested, as wafers developed with (HD3) are found to have fewer defects than wafers developed with (HD1) and (HD2) in all cases.

[0100] Example 9.2 - Heptanone and Water Developer Composition This example demonstrates the improved patterning performance obtained using water as a developer additive. Organotin oxide hydroxide photoresist patterns are developed using a developer based on a blend of 2-heptanone and water. A significant reduction in microbridging defects is demonstrated using high resolution imaging.

[0101] A developer consisting of a mixture of 2-heptanone and H2O was prepared by mixing 18 MΩ DI H2O in 2-heptanone (trace H2O concentration was 150 ppm) to give the final concentrations shown in Table 3. The final concentrations were verified by Karl Fischer titration.

[0102] [Table 3]

[0103] As shown in Example 2, organotin oxide hydroxide photoresist precursor solutions and photoresist films were prepared and processed to form line-space patterns on 32 nm pitch. Developers HW1-HW4 were used in the developing step. All wafers were washed with their corresponding developer. Each of the four developer solutions was tested on wafers treated with PEB at 140°C, 160°C, and 180°C. E in FIG. size The fitted defect counts per 150 images for the 16p32 field on each wafer are plotted against the PEB temperature (at 16p32). The PEB temperature for each wafer is indicated by the data point labels. For all tested PEBs, there is a trend towards fewer defects as the HO concentration increases, with wafers developed in solution (HW4) (8000 ppm) showing a 2-3 times reduction in microbridge density, 2 mJ / cm compared to wafers developed in solution (HW1) containing only traces (150 ppm) of HO. 2 Typical dose shifts of less than 100 μm are shown.

[0104] Example 10. 2-Heptanone and 1,2-Hexanediol Developers with Various Washing Conditions This example demonstrates the improved patterning performance obtained by rinsing with a diol additive solution. Organotin oxide hydroxide photoresist patterns are developed with a developer of 2-heptanone containing 2% by volume of 1,2-hexanediol and washed under various washing conditions. Using high resolution imaging, it is shown that rinsing with a developer containing the diol additive further reduces microbridging defects compared to rinsing with a developer without the diol additive.

[0105] Prior to formulation of the developer, all glassware was washed three times with isopropyl alcohol and baked at 100°C for 24 hours. Preparation was performed in a fume hood. A known volume of 2-heptanone (EUVR Developer, TOK America, containing 100-300 ppm H2O) was dispensed into a glass bottle. The developer (HD2) was then prepared by adding the amount required to obtain the target 2% 1,2-hexanediol additive by volume to the bottle via graduated cylinder or autopipette. The solution was capped and placed on a shaker table to mix thoroughly.

[0106] The wafers were coated, exposed, developed, washed and analyzed according to Example 2.

[0107] Twelve wafer samples were subjected to a post-exposure bake temperature of 160° C. and then developed in developer (HD2). After development, one of four wash conditions was used.

[0108] The microbridging defect analysis method described in Example 2 was applied to the resulting line-space patterns using a target CD of 16 nm. The fitted average defect counts per 150 images of the 16p32 fields for the three wafers in each cleaning condition in FIG. 18 were plotted. Error bars in the figure represent plus or minus one standard deviation. In cleaning condition (A), no cleaning was performed. In cleaning condition (B), cleaning was performed using solution (HF0) for 10 seconds. In cleaning condition (C), cleaning was performed using solution (HD2) for 10 seconds. In cleaning condition (C), cleaning was performed using solution (HF0) for 10 seconds followed by cleaning using solution (HD2) for 10 seconds.

[0109] As shown in Figure 18, cleaning condition (B) had the highest defect rate and variability. Cleaning condition (D), a two-step cleaning with (HF0) followed by (HD2), was found to reduce defects compared to cleaning condition (B). Cleaning condition (A), which did not include a cleaning step, reduced defects by more than three times compared to cleaning condition (B), with a relative standard deviation of about 14%. Cleaning condition (C) had the lowest number of defects per 150 images and reduced wafer-to-wafer variability.

[0110] This example shows that a single rinse with a diol-containing solution (HD2) reduces microbridging defects compared to no rinse and rinse with a solvent without the diol additive. Surprisingly, the single rinse with a diol-containing solution produced significantly fewer defects than a two-step rinse using a diol-containing solution (HD2) as the second step.

[0111] Example 11. PGMEA and Acetic Acid Developer Compositions Using Hexagonal Column Patterns This example demonstrates the improved performance for hexagonal pillar patterning obtained using acetic acid as a developer additive. Organotin oxide hydroxide photoresist hexagonal pillar patterns were developed using a developer with a blend of PGMEA and acetic acid and compared to 2-heptanone developer. A significant reduction in microbridging defects is demonstrated using high resolution imaging.

[0112] Organotin oxide hydroxide photoresist precursor solutions and photoresist films were prepared and processed as described in Example 2, except that the resist-coated substrates were exposed and patterned using the following PAB and the following process: A hexagonal array of 23 nm diameter pillars with a pitch of 40 nm vertically and 70 nm horizontally was projected onto each coated wafer at constant focus using an ASML NXE:3300B EUV scanner with a numerical aperture of 0.33 and hexapole illumination. After each exposure, the wafer was stepped to create a roughly annular array of fields centered around the center of the wafer at various exposure doses.

[0113] Developers (PA2) and (PA3) were prepared by mixing acetic acid and PGMEA as shown in Example 5. All wafers were rinsed with the corresponding developer. The developers were tested on wafers processed with PEB at 170° C. and 190° C. and compared with (HF0). FIG. 19 shows the EUV of wafers processed with (a) 170° C. post-exposure bake temperature and (HF0) developer, (b) 190° C. post-exposure bake temperature and (PA2) developer, and (c) 190° C. post-exposure bake temperature and (PA3) developer. sizeRepresentative SEM images of the E size The values ​​of and 3σ LCDU of the image pillars (three times the standard deviation of the CD of the pillars measured per image) are shown. The microbridge defect analysis method described in Example 2 was adapted to detect microbridges between pillars using the image analysis software KOLONA (stylized KOΛONA). The fitted average defect counts per 150 images of 27 nm CD pillar patterns printed on a 70x40y hexagonal grid are listed in FIG. 19 for each condition. It was found that wafers processed with PEB at 190° C. and developed with solutions (PA2) and (PA3) exhibited significantly lower microbridge defects and image LCDU compared to wafers processed at 170° C. and developed with solution (HF0). Compared to (HF0), improved patterning performance with acetic acid-containing developer was obtained even at lower dose vs. size.

[0114] Example 12. Primary and secondary alcohol developer compositions In this example, the improved patterning performance obtained using primary and secondary alcohols as developer additives is demonstrated. Organotin oxide hydroxide photoresist patterns were developed using the primary alcohol n-propanol and the secondary alcohol propylene glycol methyl ether and compared to 2-heptanone. A significant reduction in microbridging defects is demonstrated using high resolution imaging.

[0115] The wafers were coated, exposed, developed, washed and analyzed according to Example 2.

[0116] Developers containing neat solvents (HF0) (2-heptanone, TOK America), (PG0) (propylene glycol methyl ether, PGME, Sigma Aldrich, 99.5%) and (NP0) (n-propanol, Sigma Aldrich 99.5%) were used as received by the manufacturer. Each of the three developers was tested on wafers treated with PEB at 160° C. and 180° C. All wafers were washed with the corresponding developer. The micro-bridging defect analysis method described in Example 2 was applied to the resulting line-space patterns using a target CD of 18 nm printed by overexposure of the projected 16p32 image.

[0117] Representative SEM photographs captured from 32 nm pitch pattern fields with average line CD closest to 16 nm are presented for each wafer in Figure 20. The predicted dose (mJ cm) for each photograph is -2 ), line CD (nm), and LWR (nm) are shown. In comparison to (HF0), increased dose, reduced LWR, and improved line quality are generally observed for (PG0) and (NP0) in terms of visible microbridge defects at comparable PEB. A larger increase in dose is observed for the (NP0) developer, while a larger improvement in linewidth roughness is observed for (PG0). Figure 21 shows a log-linear plot of the number of defects counted per field for 18 nm lines on 32 nm pitch as a function of dose required to print a 16p32 pattern from the same reticle field. A reduction in the number of microbridges is observed for both (PG0) and (NP0) and at both 160°C and 180°C, compared to (HF0). It can be seen that at nearly equal dose conditions (e.g., 180°C, NP0 vs. 160°C, HF0) (NP0) reduces the microbridge density by more than 5 times. These results show improved patterning performance with primary and secondary alcohols compared to 2-heptanone, and the use of primary alcohols as developers significantly reduces microbridging defects.

[0118] The above embodiments are intended to be illustrative and not limiting. Additional embodiments are within the scope of the claims. Moreover, although the present invention has been described with respect to specific embodiments, those skilled in the art will recognize that changes in form and detail may be made without departing from the spirit and scope of the present invention. Any incorporation by reference of the above documents is limited such that no subject matter contrary to the express disclosure herein is incorporated. Unless otherwise indicated, to the extent that a particular structure, composition, and / or process is described herein with components, elements, ingredients, or other categories as suggested in the discussion, the disclosure herein should be understood to encompass specific embodiments, embodiments that include specific components, elements, ingredients, other categories, or combinations thereof, as well as embodiments that consist essentially of such specific components, ingredients, or other categories, or combinations thereof, which may include additional features that do not alter the fundamental nature of the subject matter. The use of the word "about" herein refers to the degree of error in the measurement of the particular parameter unless otherwise specified.

Claims

1. A method of developing a radiation-exposed organometallic patterning layer to form a developed patterned layer comprising an organometallic oxide / hydroxide network, the method comprising contacting the radiation-exposed organometallic patterning layer with a developer composition comprising a solvent blend, the solvent blend comprising at least two solvents, each independently having a sum of Hansen Solubility Parameters, δH+δP, of about 16 (J / cm 3 ) 1/2 or less, each of which independently has a Hansen solubility parameter δH+δP of at least about 16 (J / cm 3 ) 1/2 from about 0.25% to about 45% by volume of one or more solvents

2. The organometallic oxide / hydroxide network generally has the formula R z SnO (2-(z/2)-(x/2)) (OH) x where 0<z≦2 and 0<(z+x)≦4, and R is a hydrocarbyl group that forms a carbon bond with the tin atom, or a hydrocarbyl ligand R N 13. The method of claim 1, wherein N is a tin composition integrated into an oxo / hydroxo network.

3. Separate compound RSnX 3 3. The method of claim 1 or 2, further comprising forming the organometallic oxide / hydroxide network by depositing a precursor solution comprising:

4. The sum of the Hansen solubility parameters δH + δP is about 16 (J / cm 3 ) 1/2 4. The method of claim 1, wherein the solvent comprises an aromatic compound, an ester, a ketone, an ether, or a mixture thereof.

5. The sum of the Hansen solubility parameters δH + δP is at least about 16 (J / cm 3 ) 1/2 The method of any one of claims 1 to 4, wherein the solvent comprises acetone, a monohydroxyl alcohol, a polyhydroxyl compound, a pyrrolidone, a glycol ether, a carboxylic acid, a diol, or a mixture thereof.

6. 6. The method of any one of claims 1 to 5, wherein the solvent blend comprises 2-butanol, 2-heptanol, propylene glycol methyl ether, methanol, ethanol, propanol, isobutanol, pentanol, ethylene glycol, propylene glycol, glycerol, 2-pyrrolidone, 1-ethyl-2-pyrrolidone, N-methyl-2-pyrrolidone, ethylene glycol monomethyl ether, formic acid, acetic acid, oxalic acid, 2-ethylhexanoic acid, 1,2-hexanediol, 1,2-propanediol, 1,3-propanediol, or combinations thereof.

7. 7. The method of any one of claims 1 to 6, wherein the solvent blend comprises 4-methyl-2-pentanol, cyclohexyl acetate, dibutyl oxalate, benzene, xylene, toluene, propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate, n-butyl acetate, butyrolactone, methyl ethyl ketone, acetone, 2-butanone, cyclohexanone, 2-heptanone, 2-octanone, tetrahydrofuran, dioxane, anisole, or combinations thereof.

8. The method of any one of claims 1 to 3, wherein the solvent blend comprises 2-heptanone and / or PGMEA and about 2 to about 20 volume percent acetic acid.

9. The method of any one of claims 1 to 8, wherein the solvent blend contains no more than 10% by volume of added water.

10. forming a metalorganic patterning layer exposed to radiation, the forming of the metalorganic patterning layer comprising: forming a radiation-sensitive organometallic resist layer on a surface of the substrate by coating the substrate with an organometallic radiation-sensitive organometallic resist material; 10. The method of any one of claims 1 to 9, comprising exposing the radiation sensitive organometallic resist layer to extreme ultraviolet radiation using a patterned mask to form the radiation-exposed organometallic patterned layer, the radiation-exposed layer comprising exposed and unexposed portions.

11. Exposing the radiation sensitive organometallic resist layer to a radiation beam of about 200 mJ / cm 2 Extreme ultraviolet radiation at a dose of less than 2 mC / cm at 30 kV 2 11. The method of claim 10, comprising exposing to an electron beam:

12. 12. The method of any one of claims 1 to 11, wherein the contacting step is performed using a puddle, dip, spin coating, or spraying method in which the developer composition is applied to the surface of the radiation exposed organometallic patterning layer and dried by spinning or blowing for a selected period of time between about 2 seconds and about 30 minutes.

13. The method of any one of claims 1 to 12, further comprising washing the developed pattern with a washing liquid, the washing liquid containing the developer composition.

14. 14. The method of any one of claims 1 to 13, further comprising baking the radiation-exposed organometallic patterning layer at a temperature of from about 120°C to about 190°C (PEB temperature) prior to contacting the radiation-exposed organometallic patterning layer with the developer composition.

15. 15. The method of claim 14, wherein the duration of contact, the PEB temperature, and the developer composition are selected to obtain a desired feature size and / or a desired defectivity rate in the developed patterned structure.

16. The method of any one of claims 1 to 15, wherein the developed patterned layer has an average linewidth roughness of about 5 nm or less.

17. The method of any one of claims 1 to 16, wherein the developer composition further comprises one or more modifying additives, the developer composition comprising up to about 5% by weight of said additives.

18. 18. The method of any one of claims 1 to 17, wherein the radiation exposed organometallic patterning layer has an initial dry thickness before contacting with a developer composition and a final dry thickness after contacting with a developer composition, the initial dry thickness being from about 1 nm to about 50 nm.

19. either depositing a material based on the developed patterned layer or etching the substrate based on the developed patterned layer; The method of any one of claims 1 to 18, further comprising removing the developed patterned layer to form a processed substrate.

20. 1. A method of developing a radiation-exposed organometallic patterning layer comprising an organometallic oxide / hydroxide network, the method comprising contacting the radiation-exposed organometallic patterning layer with a developer composition comprising from about 0.25% to about 45% by volume of a solvent blend of water, alcohol, glycol ether, pyrrolidone, lactone, carboxylic acid, or combinations thereof, and at least 55% by volume of a ketone, ether, ester, or combinations thereof.

21. 21. The method of claim 20, wherein the contacting step is performed using a puddle, dip, spin coating, or spraying method in which the developer composition is applied to the surface of the radiation-exposed organometallic patterning layer and dried by spinning or blowing for a selected period of time between about 2 seconds and about 30 minutes.

22. 22. The method of claim 20 or 21, further comprising washing the developed pattern with a washing liquid, the washing liquid containing the developer composition.

23. 23. The method of any one of claims 20 to 22, further comprising baking the radiation-exposed organometallic patterning layer at a temperature of from about 120°C to about 190°C (PEB temperature) prior to contacting the radiation-exposed organometallic patterning layer with the developer composition.

24. 24. The method of claim 23, wherein the duration of contact, the PEB temperature, and the developer composition are selected to obtain a desired feature size and / or a desired defectivity rate in the developed patterned structure.

25. 25. The method of any one of claims 20 to 24, wherein the developed patterned layer comprises a plurality of periodically arranged lines, and the developed patterned layer has an average line width roughness of about 5 nm or less.

26. The method of any one of claims 20 to 25, wherein the developer composition further comprises one or more modifying additives, the developer composition comprising up to about 5% by weight of said additives.

27. 27. The method of any one of claims 20 to 26, wherein the radiation exposed organometallic patterned layer has an initial dry thickness before contacting with a developer composition and a final dry thickness after contacting with a developer composition, the initial dry thickness being from about 1 nm to about 50 nm.

28. either depositing a material based on the developed patterned layer or etching the substrate based on the developed patterned layer; The method of any one of claims 20 to 27, further comprising removing the developed patterned layer to form a processed substrate.

Citation Information

Patent Citations

  • High-resolution patterning compositions and corresponding methods based on organometallic solutions

    JP2018502173A

  • Organotin oxide hydroxide patterning compositions, precursors and patterning

    JP2019500490A

  • Organometallic photoresist developer compositions and processing methods

    JP2022526031A